Conjugate Heat Transfer Computation for Evaluation of Single-Blow Method for Compact Fin-Tube Heat Exchangers - Gil-Dal SONG; Koichi NISHINO (Journal of Thermal Science and Technology, 2008)
Computations have been carried out to evaluate heat transfer coefficients given by the single-blow method that is characterized by a transient and conjugate heat transfer problem between the fluid and the solid. Both heat conduction and convection equations are solved numerically to obtain the transient fluid and fin temperature distributions. Finite volume solutions indicate that the fin temperature distribution of the single-blow method varies with time and position and that the fluid temperature distribution of the single-blow method is close to that observed in the steady-state computation specified with the constant wall temperature condition. It is found that the local heat transfer coefficient resulting from the single-blow method is almost identical to that from the steady-state constant wall temperature computation and is nearly time-independent.